Nuclear dynamics and ionization of diatomic molecules in intense laser fields - Magrakvelidze, Maia (Kansas State University, 2009)
In this work we studied the dynamics of deuterium molecules in intense laser fields both experimentally and theoretically. For studying the dynamics of the molecule on a time scale that is less than the period of the laser field (2.7 fs for 800 nm), an advanced experimental technique: COLTRIMS (cold target recoil ion momentum spectroscopy) was used. COLTRIMS allows studying the nuclear dynamics without using attosecond laser pulses. This thesis consists of two main parts. In the first part we deduced the angular dependence of the ionization probability of the molecule without aligning the molecules, by measuring the relative angle between a deuteron resulting from field dissociation and an emitted electron using electron-ion coincidence measurements with circularly polarized light in COLTRIMS. We found out that for 50 fs pulses (1850 nm wavelength and 2 x10[superscript]14 W/cm[superscript]2 intensity), D[subscript]2 molecules are 1.15 times more likely to be ionized when the laser field is parallel to the molecular axis than when the laser field is perpendicular. This result agreed perfectly with the result from our ab initio theoretical model and also with predictions of the molecular Ammosov-Delone-Krainov (mo-ADK) theory. In the second part of this work we calculated the time evolution of an initial nuclear wave packet in D[subscript]2[superscript]+ generated by the rapid ionization of D[subscript]2 by an ultra short laser pulse. We Fourier transformed the nuclear probability density with respect to the delay between the pump and probe pulses and obtained two-dimensional internuclear-distance-dependent power spectra which serve as a tool for visualizing and analyzing the nuclear dynamics in D[subscript]2[superscript]+ in an external laser field. We attempt to model realistic laser pulses, therefore in addition to the main spike of the pulse we include the Gaussian pedestal. The optimal laser parameters for observing field-induced bond softening and bond hardening in D[subscript]2[superscript]+ can be achieved by varying the intensity, wavelength, and duration of the probe-pulse pedestal. Despite the implicit “continuum wave” (infinite pulse length) assumption the validity of the “Floquet picture” is tested for the interpretation of short-pulse laser-molecule interactions.
Keywords: molecular dynamics; ionization rate; Physics, Atomic (0748)